Walter, Archdeacon of Thérouanne: the life of Count Charles of Flanders and the life of Lord John, Bishop of Thérouanne - Gualterus, Tervanensis (Corpus Christianorum in translation, 2023)
This volume revolves around three men who knew each other well, oversaw the political and spiritual life of much of northern France and Flanders during the first third of the twelfth century, and died within five years of one another: Charles the Good, count of Flanders from 1119 to 1127; John of Warneton, archdeacon of Arras from 1096 to 1099 and bishop of Thérouanne from 1099 to 1130; and their common biographer, Walter, archdeacon of Thérouanne from 1116 to 1132. The volume includes a detailed historical introduction and offers the first English translations of Walter's biographies of Charles and John and of several other texts - Lambert of Saint-Omer?s 'Genealogy of the Counts of Flanders' and its continuation, selections from Simon of Saint Bertin?s continuation of the 'Deeds of the Abbots of Saint Bertin?s' and the third 'Genealogy of the Flemish Counts (Flandria generosa)', and the inquest into the murder of Charles the Good. The works translated in this volume are the principle sources concerning the reign and assassination of Charles the Good and the bishopric of John of Warneton that have not yet been translated into English. This volume will be of particular interest to scholars of medieval Flanders and to medieval legal, ecclesiastical, political and social historians in general